Leading with ethics and establishing an ethical culture - V Basil Hans (Journal of Advanced Research in Economics and Business Management, 2026)
Ethical leadership is very important for creating and keeping an ethical culture in businesses. Leaders that are honest, fair, and responsible set norms for how people should act that affect how employees think and act. This article looks at how ethical leadership creates an ethical culture in an organisation by fostering open communication, supporting ethical principles, and making decisions and incentive systems that support ethical behaviour. Utilising ethical leadership theory and organisational culture frameworks, the study elucidates the mechanisms by which leaders function as role models and foster environments conducive to ethical awareness and responsibility. The results indicate that ethical leadership fortifies trust, amplifies employee commitment, and diminishes unethical practices by integrating ethical concepts into routine organisational operations. The essay ends by saying that organisations that want to be there for a long time, be trusted, and have good relationships with their stakeholders need to promote ethical leadership.